Pengembangan multimedia pembelajaran matematika dengan swishmax - Dian Ratnawati; Amalia Fitri (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The use of multimedia learning today is an absolute demand in the world of education. However, there are still many schools that have not implemented multimedia in the learning process. Learning that is done in the classroom is still less effective, motivation and ability to understand students' concepts are still lacking. Learning multimedia will be developed with the SwiSHmax application to get valid criteria to be able to overcome the problems that exist in schools. The type of research used is Research and Development (RnD) research. The development steps used in this study adapt the development steps of ADDIE starting from the analysis phase, the design stage, the development stage, the application stage, and the evaluation stage. The validation questionnaire results showed the average validator rating reached 4.22, which means that the multimedia that was developed was included in the valid category. The results of the calculation of the practicality value of learning multimedia were 87.97%. Based on the results of the validation and practicality of learning multimedia, it can be concluded that this learning multimedia is included in the appropriate category for use in learning.